SUSPECTS IN CRIMINAL INVESTIGATIONS OF RAPE - Marinković, Darko M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Investigations of sexual assaults mostly focus on victims and their credibility, which may cause lack of firm evidence in relation to suspects. Given the fact that the criminal offence of rape is characterised by a high incidence of false reports and accusations, frequently indicating specific persons as the perpetrators, certain caution is necessary in the investigation in order to avoid false accusations and/or convictions. As regards the personality of the rapist and motives for committing a forcible sexual act, certain types or rather certain categories of perpetrators can be distinguished, although it should be noted that a large number of rapists do not belong to one category only, but rather combine characteristics of several different types. During a criminal investigation it is of vital importance to differentiate between a rape as a surprise attack and a rape as abuse of trust, as they are compatible with the nature of the suspect’s defence. The suspect shall be subjected to a forensic examination in the course of the investigation in order to find traces which prove vaginal, anal or oral penetration, coerced sexual intercourse and identity of the rapist. While conducting an interrogation of a suspected rapist, a crime investigating officer shall use either factual or emotional approach to his interviewee, depending on his psychological and motivational characteristics. In this regard, the factual approach is believed to be more efficient with anger rapists and sadistic rapists, whereas the compassionate approach gives good results with the gentlemen-rapists and partly with the power asserting rapists.